ISLAMIC LEGAL BASIS FOR MARRIAGE - Mukarrom, Azmil (Jurnal Kajian Hukum Islam, 2018)
Marriage is common and applies to all of its creatures, whether in humans, animals, or herbs. It is a chosen way by God. In Islamic religion, God encourages us to perform marriage. Marriage is a process in which a woman and a man unite their relationships in a family bond with the aim of organizing home life and offspring. Marriage in Islam is a sacred process, having certain manners and cannot be done in random. If the marriage is not performed based on Islamic law, then the marriage can be an act of adultery. Therefore, we as Muslims must know the tips of marriage in accordance with the rules of Islamic religion so that our marriage is judged by Allah SWT